Implementasi Metode Mengajar Menurut Perspektif Q.S An Nahl: 125 Oleh Guru Pendidikan Agama Islam Dalam Meningkatkan Prestasi Siswa Di SMA Swasta Islam Terpadual Izzah - Br Sinaga , Ismi Asrida; Idris, Muhammad; Muhklis (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2024)
This study aims to determine the implementation of learning methods contained in the Al-Qur'an Surah An-Nahl / 16 verse 125 on student achievement. Knowing effective learning methods to improve student achievement at the Al Izzah Integrated Islamic Private High School, Batu Bara Regency. This study uses a descriptive qualitative research method. Where in this study, the data is displayed as it is without manipulation or other treatment. This study was conducted to study, analyze and describe data and facts. The data collection techniques through observation, interviews and documentation. The results of this study are the implementation of learning methods according to the perspective of the Al-Qur'an Surah An Nahl 125 which is applied at the Al Izzah Integrated Islamic Private High School. In the researcher's research, the learning methods contained in the Qur'an Surah An Nahl 125 are wisdom that can be applied through experimental learning methods, lecture methods by providing motivation and role models. Mau'idzatul hasanah, good advice that can be applied in lecture methods, discussion methods by providing good advice and motivation. Jidal is applied in the discussion learning method by implementing differences of opinion with the aim of raising awareness and conveying the truth.